Pengaruh Aplikasi Let’s Read dan Literacy Cloud terhadap Keterampilan Membaca pada Siswa Kelas IX SMPN 5 Kota Serang Tahun Ajaran 2022/2023 - Farah Putri Oktaviani; Tatu Hilaliyah; Ilmi Solihat (Peneliti.net, 2023)
Short story reading skills are one of the competencies that students in Indonesian language subjects must master. One way to improve reading skills is to use suitable media. This study aimed to determine the effect of Let's Read and Literacy Cloud applications on Reading Skills in Class IX Students of SMPN 5 Serang City in the 2022/2023 Academic Year. This research is quasi-experimental with a control group pretest-posttest design that uses pretest and posttest for the effect of treatment on short story reading skills. The sample in this study amounted to 68 people, divided into 34 people in the experimental group and 34 in the control group. Statistical analysis was carried out using the t-test. The results showed that the Let's Read application had an influence on improving students' skills in reading short stories, and the Literacy Cloud application also had an impact on improving students' skills in reading short stories. The analysis results show that the Lets Read application has a higher effect on students' reading skills than the Literacy Cloud application. This indicates that the use of the Let's Read application is expected to be increased so that it can improve students' short story reading skills more optimally.